From Accelerated Accumulation to the Socialist Market Economy Chinese Economic Discourse and Development from 1953 to Present - Brodsgaard, Kjeld Erik; Rutten, Koen (Brill, 2017)
The book is based on the hypothesis that a systematic analysis of the Chinese economic discourse is necessary in order to understand the underlying logic of Chinese economic development.Â The majority of works on the subject see China's economic development as a linear process of marketization or "growing out of the plan". In contradistinction to the prevailing paradigm, this book underlines that basic economic issues such as over-investment and unbalanced development continue to frame economic policy-making. The book is also unique in basing the narrative on a rich collection of Chinese language material.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: History; History; Electronic books